The Effectiveness of The PjBL Model on Students' Critical Thinking Skills in Physics Learning: A Bibliometric Analysis and Systematic Literature Review - Alia Cahyani; Lutfiatussolihah Lutfiatussolihah (Indonesian, 2023)
Critical thinking skills are among the essential competencies that need to be developed in 21st-century learning. One of the instructional models widely used to foster these skills is Project-Based Learning (PjBL). This study aims to analyze research trends and the effectiveness of Project-Based Learning in improving students' critical thinking skills through a combination of bibliometric analysis and a Systematic Literature Review (SLR). The study employed a descriptive method, with bibliometric analysis conducted using VOSviewer and the SLR carried out following the PRISMA 2020 guidelines. Articles were retrieved from Google Scholar using the Publish or Perish software, covering publications from 2014 to 2023. The selection process identified 21 articles that met the inclusion criteria for analysis. The bibliometric analysis revealed that the existing literature is dominated by studies on the implementation of PjBL in physics education, with recent developments focusing on STEM integration, instructional material development, and the use of digital technologies. The SLR findings indicated that all selected studies reported a positive effect of Project-Based Learning on students' critical thinking skills, as evidenced by improvements in N-Gain scores, statistically significant results, and effect size measures. Therefore, Project-Based Learning has been demonstrated to be effective in enhancing students' critical thinking skills in 21st-century education.